AL-JUMLAH AL-MUTSBATAH FI QISHSHAH ASH-SHAUT AL-MUKHIF: DIRASAH TAHLILIYYAH TAGHMIMIYYAH LI KENNETH L. PIKE - M. Fadillah; Abdul Muntaqim Al Anshory; Yofrizal Fovira (Afshaha: Jurnal Bahasa dan Sastra Arab, 2025)
This study analyzes the sentence structure in the short story "Al-Shaut Al-Mukhif" by Hasan Muhammad Kamil using Kenneth L. Pike’s Tagmemic approach. The research employs a qualitative method with data analysis based on the Miles and Huberman model, which includes three main stages: data reduction, data display, and conclusion drawing. The aim of the study is to identify the patterns of positive sentence structures within the text. The results indicate that several positive sentences in the short story exhibit the patterns P + S + Adverbial and S + P + Complement. The analysis is based on the four main elements in Tagmemic theory: slot, class, role, and cohesion. These elements contribute to the cohesion of sentence structures, forming clear meaning and establishing systematic relationships among the components. This study demonstrates that the Tagmemic approach is not only relevant for formal linguistic studies but also highly effective in examining the relationship between structure and meaning in literary works, particularly short stories.